Clinical characteristics in patients with asymmetric idiopathic pulmonary fibrosis. (October 2016) - Callahan, Sean J.; Xia, Meng; Murray, Susan; Flaherty, Kevin R.
Abstract: Background: A group of patients with idiopathic pulmonary fibrosis (IPF) presents with disease affecting one lung markedly more than the other. At this time, it is unclear how this population differs from those who present with more symmetric disease. We sought to explain the characteristics of the asymmetric group and how their disease progresses. Methods: In this retrospective case-control study we accessed an interstitial lung disease (ILD) database and identified 14 asymmetric IPF cases via high-resolution computed tomography (HRCT) scoring of each lung lobe's disease severity. We identified 28 symmetric IPF controls from the same database using the same methods, and compared the clinical features of each group. Results: Patients with asymmetric disease exhibited similar demographics as those in the general IPF population; they were predominantly male (64%), elderly (69 years old), and used tobacco (57%). We found a trend toward significantly increased all-cause mortality in the case population two years following diagnosis (p = 0.089). Pulmonary function tests were significantly lower in the case group at the time of diagnosis, then both groups experienced gradual decline. We found no statistically significant differences in number of IPF exacerbations (cases 43%, controls 39%, p = 0.824) and gastro-esophageal reflux (both groups 50%). Conclusion: Patients with asymmetric IPF resemble patients in the general IPF population but may have a lower overall survival rate. Further systemic factors may be studied to identify reasons for disease asymmetry and clinical decline in this population. Highlights: IPF associations such as GER and smoking cannot identify patients with asymmetric IPF. Asymmetric disease resembles classic IPF patterns in terms of age, gender, and race. Patients with asymmetry present with worse pulmonary function at the time of diagnosis. Asymmetric IPF is associated with a trend toward increased two-year mortality. Pulmonary decline in patients with asymmetric IPF mirrors those with symmetric disease.